Efektivitas Program Parenting di Tk IT Insan Mulia Wonosobo sebagai Pembentukan High Self-Esteem Anak Usia Dini - Dita Nurul Istiqomah; Mukromin Mukromin; M. Yusuf Amin Nugroho (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the influence and magnitude of the influence of parenting programs on the formation of high self-esteem in early childhood at TK IT Insan Mulia Wonosobo. Using an ex post facto quantitative approach, data were obtained from 60 parents of children aged 5–6 years through questionnaires and observations. The results of the analysis showed that there was a significant influence of parenting programs on the formation of children's self-esteem (Sig. value = 0.036 <0.05) with a contribution of 7.4%. Although significant, the effect was still low, indicating that 92.6% of children's self-esteem was also influenced by other factors such as the social environment and personal experiences. This finding reinforces the importance of active parental involvement in parenting as school partners in supporting children's psychological development.